Psoas Muscle Index Can Be Used to Predict Long-Term Mortality in Young Male Patients With Acute-on-Chronic Liver Failure - Xu, Manman; Li, Tongzeng; Kong, Ming; Geng, Nan; Song, Wenyan; Guo, Guanya; Duan, Zhongping; Han, Ying; Chen, Yu (Frontiers in Nutrition, 2022)
Objective The use of psoas muscle index (PMI) in acute-on-chronic liver failure (ACLF) has not been reported, and the aim of this study was to evaluate the predictive value of PMI for the prognosis of patients with ACLF. Methods In this study, male ACLF patients who underwent abdominal CT between 2015 and 2019 in our center were included to analyze the association between PMI and 1-year mortality in male ACLF patients, and subgroup analyses were performed according to age stratification (≤ 40 and >40 years). Results We included 116 male patients with confirmed ACLF, with a mean PMI of 5.98 ± 1.68 cm2/m2 and a 1-year mortality of 51.7% (60). Univariate COX regression analysis showed that PMI was a protective factor [hazard ratio (HR), 0.851, 95%CI: 0.734–0.987] for 1-year mortality in male patients with ACLF. Nevertheless, multivariate analysis did not find an independent relationship between PMI and 1-year mortality. Subgroup analysis by age found that adjusted for MELD score, PMI was independently associated with 1-year mortality in young (age ≤ 40 years) male patients with ACLF (HR 0.689, 95% CI: 0.496–0.958). While no effect of PMI on 1-year mortality in non-young (age > 40 years) male ACLF patients was found. Correlation analysis found that there was no significant correlation between PMI and age in young (age ≤ 40 years) male ACLF patients, but, PMI decreased with age (r = −0.246, P < 0.05) in non-young (age > 40 years) male ACLF patients. Conclusion PMI was found to be associated with 1-year mortality in male ACLF patients, especially in patients younger than 40 years, PMI predict 1-year mortality independent of MELD score.